Calculated haemorheological profile and laboratory parameters in new diagnosed multiple myeloma patients: retrospective analysis according to survival - Melania Carlisi; Rosalia Lo Presti; Corinne Spoto; Salvatrice Mancuso; Sergio Siragusa; Gregorio Caimi (Therapeutic Advances in Hematology)
Background: Multiple myeloma is a malignant haematological neoplasm characterised by clonal proliferation of plasma cells, with a complex clinical picture, and a significant impact on patient survival, in which the prognosis evaluation of patients is of great importance. Objectives: In this single-centre retrospective analysis, performed in a group of newly diagnosed multiple myeloma patients, we examined several clinical and laboratory parameters in order to evaluate their trend according to survival of patients. Design: We collected data from 190 newly diagnosed multiple myeloma evaluated at the Hematology Division of the ‘Paolo Giaccone’ University Hospital of Palermo from 1 January 2017 to 30 September 2022. Specifically, we performed our analysis in the entire cohort of patients and also in the specific disease isotype. Methods: We evaluated simple and low-cost laboratory and haemorheological parameters, the latter obtained in a calculated way. The primary endpoint was to evaluate the trend and the differences of these parameters in the study population, divided into two specific groups, deceased and survivors after a specific observation period of almost 7 years. Results: In the entire cohort of multiple myeloma patients, we observed a mortality rate of 40%, of whom 36.4% were men and 43.1% were women. Among the patients who died, in comparison with those who survived, it is significantly evident the increase in age, in red cell distribution width (RDW), RDW%/albumin ratio and in the RDW%/haemoglobin ratio; moreover, in the same patients subgroup, we observed a reduction in haematocrit, total serum protein, calculated whole blood viscosity (evaluated according to the de Simone formula), serum albumin, albumin/fibrinogen ratio and in haemoglobin levels. Conclusion: The obtained data can represent a possible starting point for subsequent targeted analyses, aimed at studying the prognostic value of each individual parameter considered, favouring an increasingly complete and immediate prognostic evaluation of patients.